Planning for outdoor play: Government and family decision-making. (10th November 2019) - Sterman, Julia J.; Naughton, Geraldine A.; Bundy, Anita C.; Froude, Elspeth; Villeneuve, Michelle A.
Abstract: Background: Despite indisputable developmental benefits of outdoor play, children with disabilities can experience play inequity. Play decisions are multifactorial; influenced by children's skills and their familial and community environments. Government agencies have responsibilities for equity and inclusion of people with disabilities; including in play. Aim: This multiple-perspective case study aimed to understand outdoor play decision-making for children with disabilities from the perspectives and interactions of: local government and families of primary school-aged children with disabilities. Material and method: Five mothers, four local government employees, and two not-for-profit organization representatives participated in semi-structured interviews. Inductive and iterative analyzes involved first understanding perspectives of individuals, then stakeholders (local government and families), and finally similarities and differences through cross-case analysis. Findings: Local government focused more on physical access, than social inclusion. Local government met only minimal requirements and had little engagement with families. This resulted in poor understanding and action around family needs and preferences when designing public outdoor play spaces. Conclusion and significance: To increase meaningful choice and participation in outdoor play, government understanding of family values and agency around engagement with local government needs to improve. Supporting familial collective capabilities requires understanding interactions between individuals, play, disability, and outdoor play environments.